Electrically Conductive Polyaniline/Silk Fibroin Composite for Ammonia and Acetaldehyde Sensing. Issue 2 (February 2018) - Ahmad, Sharique; Sultan, Adil; Mohammad, Faiz
In this study, camphorsulphonic acid-doped conducting polyaniline/silk fibroin (Pani/SF) composites were prepared by in-situ polymerisation. The Pani/SF composite fibres were characterised by using Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy, thermogravimetric analysis, scanning electron microscopy and digital photographs. Results indicated that the Pani was successfully coated on silk fibroin. The electrical properties of Pani/SF composite fibres were influenced by the extent of loading of aniline monomers. The as-prepared material was studied as a sensing material by observing the change in their electrical conductivity on exposure to ammonia and acetaldehyde, followed by ambient air at room temperature. It was found that the composite fibres showed good reversibility and conductivity decreased on exposure to higher concentration of ammonia and acetaldehyde vapours at room temperature.